2012
DOI: 10.1080/10538712.2012.689424
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse in the Anglican Church of Australia

Abstract: This article reports on a retrospective study of cases of child sexual abuse complaints made against clergy, other employed pastoral staff, and volunteers in the Anglican Church of Australia between 1990 and 2008. There were 191 allegations of sexual abuse made by 180 complainants against 135 individuals. Twenty-seven of those 135 had more than one complaint made against them. Three-quarters of all complainants were male. The most likely explanation for the large proportion of abused males is that the church g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…It was found that CSA-W usually differed from child sexual abusers not working with children (CSA) in so far as they were older, better educated, and less likely to be in an adult relationship, while they did not differ concerning the frequency of having experienced sexual abuse themselves (Colton, Roberts, & Vanstone, 2010;Sullivan & Beech, 2004;Turner et al, 2014a). Recently, Turner and colleagues (2014a) reported that CSA-W were more likely to show indicators for pedophilic sexual interests while at the same time they showed fewer indicators for antisocial behaviors and reported fewer previous problems with alcohol compared to CSA not working with children (Turner et al, 2014a; see also Langevin, Curnoe, & Bain, 2000;Parkinson, Oates, & Jayakody, 2012;Spröber et al, 2014;Sullivan, Beech, Craig, & Gannon, 2011 for similar findings). Due to this constellation of risk factors it was concluded that CSA-W seem to exhibit more specific risk factors for sexual reoffending while they are not so much in danger for general or violent reoffending (Turner et al, 2014b).…”
Section: Characteristics and Risk Factors Of Child Sexual Abusers Wormentioning
confidence: 98%
“…It was found that CSA-W usually differed from child sexual abusers not working with children (CSA) in so far as they were older, better educated, and less likely to be in an adult relationship, while they did not differ concerning the frequency of having experienced sexual abuse themselves (Colton, Roberts, & Vanstone, 2010;Sullivan & Beech, 2004;Turner et al, 2014a). Recently, Turner and colleagues (2014a) reported that CSA-W were more likely to show indicators for pedophilic sexual interests while at the same time they showed fewer indicators for antisocial behaviors and reported fewer previous problems with alcohol compared to CSA not working with children (Turner et al, 2014a; see also Langevin, Curnoe, & Bain, 2000;Parkinson, Oates, & Jayakody, 2012;Spröber et al, 2014;Sullivan, Beech, Craig, & Gannon, 2011 for similar findings). Due to this constellation of risk factors it was concluded that CSA-W seem to exhibit more specific risk factors for sexual reoffending while they are not so much in danger for general or violent reoffending (Turner et al, 2014b).…”
Section: Characteristics and Risk Factors Of Child Sexual Abusers Wormentioning
confidence: 98%
“…In addition to these inquiries there are inquiries conducted by organisations themselves, for example, Olsson and Chung's "Report of the board of inquiry: Into the handling of claims of sexual abuse and misconduct within the Anglican diocese of Adelaide" [29] established by the Synod of the Diocese of Adelaide in 2003, and Parkinson, Oates and Jayakody's "Study of reported child sexual abuse in the Anglican Church" [30]. Commissioned by the Church's Professional Standards Commission, this latter study aimed to examine abuse reports in the Australian Anglican church.…”
Section: Current and Previous Inquiriesmentioning
confidence: 99%
“…Commissioned by the Church's Professional Standards Commission, this latter study aimed to examine abuse reports in the Australian Anglican church. The authors reported that while all 23 diocese were invited to participate in the research, three declined ( [30], p. 13).…”
Section: Current and Previous Inquiriesmentioning
confidence: 99%
“…However, in our study on child sex abuse in the Anglican Church, where there are no celibacy requirements, the gender pattern of victims was similar. 5 We suggested that this may have been because girls were less often left alone by their parents before and after church activities, whereas boys were less well supervised and thus at greater risk. 5 Clearly, there is no simple explanation.…”
mentioning
confidence: 95%
“…5 We suggested that this may have been because girls were less often left alone by their parents before and after church activities, whereas boys were less well supervised and thus at greater risk. 5 Clearly, there is no simple explanation. As Justice McClellan said, 'Poor practices, inadequate governance structures, failures to record and report complaints, or understating the seriousness of complaints, have been frequent' and 'If the problems we have identified are to be adequately addressed, changes must be made.…”
mentioning
confidence: 95%